Recruitment Management in An Effort to Improve The Quality of Educators at SMPIT 'Abdan Syakuro Lampu Iman Karawang - Rizal, Muhammad; Kuswandi, Aos; Nour, Muntaha (Proceeding International Conference on Education, 2023)
This study aims to analyze recruitment management in an effort to improve the quality of educators at SMPIT Lampu Iman Karawang. This study uses a qualitative method. Methods of data collection are done through observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation and verification. This research resulted in the following conclusions: 1) The quality of Educators at SMPIT Lampu Iman Karawang is relatively good; 2) Recruitment management which is carried out through the process of preparing recruitment, distributing vacancy announcements through brochures on social media, receiving new applications and selecting applicants from administrative requirements, written tests, microteaching tests and interviews; 3) Factors hindering recruitment are the difficulties in getting educators who are in accordance with the academic fields needed by schools. From the results of the study it can be concluded that with planned, measurable and objective recruitment management can improve the quality of educators.